After the Pandemic: The Future of Italian Medicine. The Psychological Impact of COVID-19 on Medical and Other Healthcare-Related Degrees Students - De Micheli, Giacomo; Vergani, Laura; Mazzoni, Davide; Marton, Giulia (Frontiers in Psychology, 2021)
Objective: The study aimed to explore the psychological symptoms and the readiness to fight the pandemic of the new generation of healthcare professionals: medical and other health care degrees students Methods: We enrolled a total of 509 medical and healthcare related degrees students during the second outbreak of COVID-19 in Italy. We examined their psychological symptoms with the GHQ-12 and their readiness to fight the pandemic together with their academic career status, their relationship with the university and their emotional reactions to the pandemic with Visual Analogue Scales Results: We retrieved a GHQ mean of 21.65 (SD=4.63), and a readiness of fight the pandemic mean of 53.58 (SD=31.49). Perceived control has an effect on both the two variables: a negative effect on psychological symptoms and a positive effect on the readiness to fight for the pandemic. The other variables with an effect were stress, loneliness and anger that had a significant and positive effect on psychological symptoms. Age and fear for patients had a significant positive effect on readiness to fight for the pandemic, while years of attendance had a significant but negative effect. Conclusion: The impact of the pandemic on students should be considered by Universities and Institutions for the effect on their mental health. Moreover, students' readiness to fight the pandemic should be addressed regarding the appropriate role medical and healthcare related degrees students should have in pandemic contexts.